Inovasi Produk dalam Kosmetik Halal : Membangun Kepercayaan Konsumen melalui Citra Merek. - Faidil, Muh; Windarsari, Wiwin Riski; Ramadhani, Annisa; Rakib Sibiti, Raudatul Jannah; Syarifuddin, Nur Aliyah (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this study is to analyze the model of product innovation formation affecting consumer trust through brand image. This study uses a quantitative method using Accidental Sampling which produces a sample of 100 people. Data analysis used the smallest partial structural equation model of square (PLS-SEM). The findings show that product innovation in the Wardah product line has a significant and positive influence on consumer confidence. In addition, this study found that product innovation has a significant and positive impact on brand image, and brand image has a significant and positive impact on consumer trust. However, the study also revealed that brand image does not play a mediating role in the relationship between product innovation and consumer trust, as evidenced by the results of insignificant hypothesis tests. Therefore, brand image does not mediate the relationship between product innovation and consumer trust. This research contributes to the understanding of how product innovation and brand image affect consumer trust